O nome disso: Arnaldo Antunes - Costa, Maria de Fatima Sena (2008)
This research unfolds a view in regard to the poetic composition of Arnaldo Antunes and the history of his literature perpassing a complex environment of relations. In which the various literary creations are mixed. In order to understand better the way how these ideas are outripend and articulated, we rather bring his poetic production somehow nearer to the artistic tendencies, which arose at the beginning of the 20th century. These created a profound transformation in the fields of art and culture, a fact we see in the course of the whole century and still today are enduring in the contemporaneous productions through this and other poets. Based on this progression, we try to find out the models which helped them to be inspirited and also the historical marks in literature, which allow us to find out and read the processes in unreding, appropriation, scripts and literature and therewith the forms these poetical categories are reconfigured in a effort of superation. Thus a proper and autonomic literature could be achieved. The theoretical body is based and established by authors like Pierre Bourdieu, Dominique Maingueneau, Harold Bloom, Roland Barthes and some others supporting as well. We verify that the high level of scientific and technological development of the modern society provokes new social arrangements, demanding also a renewal in the social habits in our times. That lifts up, the identity of an individual in this particular society having to reveal itself in the inner of the representation systems, - and in the same way he will have to allow to be represented by the others. In the interacting movement in several fields and in the constant being inspired on through the various linguistic codes, Arnaldo Antunes demonstrates the reading of the tradions flowing to unfold itself as a revitalization of arts, standing up against the banality and materialism of the contemporaneous world, but rather that the technical and experimental profits are contributions, which permit the development and orientation of the direction his writing can have to achieve the liberty of style and the literature as such.